2004
DOI: 10.1074/jbc.m313100200
|View full text |Cite
|
Sign up to set email alerts
|

A Superfamily of Voltage-gated Sodium Channels in Bacteria

Abstract: NaChBac, a six-␣-helical transmembrane-spanning protein cloned from Bacillus halodurans, is the first functionally characterized bacterial voltage-gated Na ؉ -selective channel (Ren, D., Navarro, B., Xu, H., Yue, L., Shi, Q., and Clapham, D. E. (2001) Science 294, 2372-2375). As a highly expressing ion channel protein, NaChBac is an ideal candidate for high resolution structural determination and structure-function studies. The biological role of NaChBac, however, is still unknown. In this report, another 11 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
143
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(149 citation statements)
references
References 35 publications
1
143
2
Order By: Relevance
“…We previously identified an Na V from the marine sulfur-reducing bacterium S. pomeroyi (Na V Sp1), which is functional when expressed in mammalian cells (8), as a protein that could be highly expressed (approximately 20 mg L −1 ) in Escherichia coli membranes (15). Despite the high expression level, size-exclusion chromatography analysis of purified, detergent-solubilized Na V Sp1 revealed a broad elution profile indicative of a polydisperse sample that was not well suited to further characterization (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously identified an Na V from the marine sulfur-reducing bacterium S. pomeroyi (Na V Sp1), which is functional when expressed in mammalian cells (8), as a protein that could be highly expressed (approximately 20 mg L −1 ) in Escherichia coli membranes (15). Despite the high expression level, size-exclusion chromatography analysis of purified, detergent-solubilized Na V Sp1 revealed a broad elution profile indicative of a polydisperse sample that was not well suited to further characterization (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Functional studies of a number of bacterial Na V s have shown them to be sodium-selective (8)(9)(10)). Yet, in line with the close evolutionary relationship of Na V s and Ca V s (1-4), the bacterial Na V selectivity filter sequences also bear some sequence similarity to those of Ca V s (9,10,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] The bacteria also evolved the first precursor of the Na ϩ channel, the NaChBac expressed, for example, in Bacillus halodurans. 8 In the eukaryotes, the excitable molecules developed further; in single-cell organisms, the waves of plasmalemmal excitation began to generate through the spreading opening/closures of voltagegated channels. 9 In parallel eukaryotic organisms acquired intracellular organelles, intracellular channels dwelling in the endomembranes, and exocytotic machinery formed the basis for chemical intercellular transmission.…”
Section: Glial Explosion Forms the Human Brainmentioning
confidence: 99%
“…Their function in mammals underlies neuronal signaling, muscle contraction, and hormone secretion (1). The first bacterial voltage-gated sodium channel (NaChBac) 1 was identified from Bacillus halodurans (2), and a number of orthologs were subsequently identified, forming a superfamily (3). The function of voltage-gated sodium channels in bacteria is still a matter of debate; however, there is evidence that these channels are involved in processes such as motility, chemotaxis, and pH homeostasis (4).…”
mentioning
confidence: 99%